Parasit Ilmu Dalam Pendidikan Islam Perspektif Ihya Ulumuddin - Azmi, M. Ulul; Mushaffa, Arju; Islam, Muhammad Thoriqul; Fasya, Zaini; Hidayati, Salamah Noor (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
Imam Al-Ghazali is a prominent scholar whose intellectual legacy has become a reference in various fields of knowledge. Known for his brilliance and piety, Al-Ghazali serves as an exemplary figure, emphasizing the importance of lifelong learning as long as one’s heart continues to beat. This study employs a literature research method, gathering information from scholarly works such as books, scientific journals, credible websites, articles, and other relevant sources. The collected data are then analyzed to produce findings. The research focuses on Al-Ghazali's views on Islamic education as written in his seminal work Ihya Ulumuddin and discusses the potential diseases of knowledge that may afflict its bearers. Islamic education aims to cultivate individuals with noble character (akhlaqul karimah), ultimately bringing them closer to Allah. It encompasses: (1) Faith education, (2) Moral education, (3) Intellectual education, (4) Social education, and (5) Physical education, summarized into aqliyah (rational sciences) and muktasabah (acquired sciences). The diseases of knowledge include: (1) Arrogance, (2) Hypocrisy, (3) Fear, (4) Contentment with ignorance, (5) Extravagance, (6) Selling knowledge for worldly gain, (7) Excessive talk, (8) Failing to practice knowledge, (9) Flattering authorities with knowledge, and (10) Overstating the truth.